PENGARUH DAYA TARIK WISATA, AKSESIBILITAS DAN FASILITAS TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE PANTAI SIANGAU KABUPATEN BANGKA BARAT - Koko Ardiansyah; Sumar; Ari Agung Nugroho (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2022)
The relatively low number of tourists in Siangau Beach motivated the present writer to analyze the effects of Attractions, Accessibility and Facilities on Tourist’s Decisions to Visit Siangau Beach in West Bangka Regency. This research uses quantitative approach with a total sample of 95 respondents, who were seleted using non-probability sampling. The independent variables in this research are attraction, accessibility and facilities, while the dependent variable is decision to visit. The data we analyzed using multiple linear regression with t-test, F test and R2. The multiple regression analysis model obtained was Y= -3,209 + 0,605+ 0,580 + 0,426; The research results indicate that partially, tourist attraction, accessibility and facilities have positive and significant effect on tourists’ decisions to visit Saingau Beach in West Bangka Regency. Meanwhile the F-test results indicates that attraction, accessibility and facilities simultaneously have positive and significant effect on tourists’ decision to visit Siangau Beach in West Bangka Regency. Coefficient of determination (R2) test results indicates that the research model can explain 58,6% of tourists’ decisions to visit Siangau Beach, while 41,4% was affected by other variables outside of the research, wich can be further investigated.. Keywords: Attraction, Accessibility, Facilities, Decision to Visit